TAREKAT NAQSHABANDIYYAH KHALIDIYYAH IN MALAYSIA: A Study on the Leadership of Haji Ishaq bin Muhammad Arif - Abdul Manam Bin Mohamad al-Merbawi; Mohd Syukri Yeoh Abdullah; Osman Chuah Abdullah; Wan Nasyrudin Bin Wan Abdullah; Salmah Ahmad (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2012)
Abstrak: Tarekat Naqshabandiyyah Khalidiyyah di Malaysia: Suatu Studi Kepemimpinan Haji Ishaq bin Muhammad Arif. Tarekat Naqshabandiyyah Khalidiyyah pimpinan Haji Ishaq memilik banyak pengikut juga terkenal di kalangan tarekat di Malaysia. Artikel ini akan menelusuri kepemimpinan Haji Ishaq bin Muhammad Arif, muncul dan berkembangnya tarekat Naqshabandiyyah Khalidiyyah di Malaysia. Data dikumpulkan tidak hanya melalui manuskrip tulisan Haji Ishaq, akan tetapi juga karya-karya muridnya. Observasi lapangan juga dilakukan di beberapa situs yang diidentifikasi sebagai pusat pergerakan. Untuk memperkuat argumen-argumen data manuskrip, beberapa murid senior Haji Ishaq juga diwawancarai. Kajian ini menemukan bahwa tarekat Naqshabandiyyah Khalidiyyah pimpinan Haji Ishaq merupakan komunitas besar yang memiliki banyak pengikut dari latar belakang yang berbeda termasuk para akademisi dan profesional. Kekuatan kelompok ini tercermin dari terciptanya pusat-pusat jaringan luas di berbagai negara bagian Malaysia.Abstract: The Tarekat Naqshabandiyyah Khalidiyyah lead by Haji Ishaq has many followers and is also known especially among other tarekat followers in Malaysia. This article is navigating through the leadership of Haji Ishaq Bin Muhammad Arif, the emergence of tarekat Naqshabandiyyah Khalidiyyah  he lead and its evolution in Malaysia. Beside the data collected through the manuscript written by Haji Ishaq, his murids works were also studied. Field observations were also performed at several sites that are identified to be the centers of the movement. Also, some senior students of Haji Ishaq were interviewed to strengthen the arguments of the manuscript data. This study had discovered that tarekat Naqshabandiyyah Khalidiyyah lead by Haji Ishaq was large group with many followers, made up of diverse backgrounds, including academicians and professionals. The power of this group is reflected in the extensive network of centers that are located in several states in Malaysia.Key Words: Tarekat, Haji Ishaq bin Muhammad Arif, Naqshabandiyyah Khalidiyyah